The Role of the Center for Community Learning Activities in Providing Educational Rights to Prisoners Assisted Class IIB Serang Prison - Yulyanti Saparina Ria Yuni Lestari; Wika Hardika Legiani (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study was to determine the role of the Center for Community Learning Activities (Pkbm) in providing educational rights to prisoners inmates. This research was conducted at PKBM Bina Pengayoman Rutan Class IIB Serang using a qualitative approach. Collecting data using observation, interviews, and documentation. The results of the study found that PKBM plays a very important role in giving education rights to Correctional Families by holding teaching and learning activities for package A, B, and C equality programs. In addition to teaching and learning activities, skills training is also held by making handicrafts and training in the arts of music. The role of PKBM cannot be separated from the supporting factors from the Serang City Education Office and the Serang City Library and Archives Service which always provide learning resources for PKBM students. However, there are inhibiting factors in PKBM activities in providing educational rights to Correctional Assisted Residents, namely Correctional Assisted Residents do not understand the rights they must obtain while serving their detention period.